In silico investigation of bioactive compounds from Ginkgo biloba as alternatives to non-steroidal anti-inflammatory drugs - Jai, Jyotsna; Yosiano, Stephanie Angela; Trisna, Tifara Elaine; Rosaceae, Agnes Maria; Kurniawan, Laurentius Hardy; Nurdiansyah, Rizky (Indonesia International Institute for Life Sciences, 2022)
Non-steroidal Anti-inflammatory Drugs (NSAIDs) are common over-the-counter drugs that are used for numerous inflammation-associated ailments. Despite their widespread consumption, these synthetic drugs are not without side effects. Adversities caused by NSAIDs range from simple nausea and vomiting to fatal conditions such as hypertension, gastrointestinal bleeding and diminished renal function. There is thus a need to develop novel alternatives to these drugs which possess comparable efficacies. Phytocompounds are attractive alternatives for a plethora of medicines used for various disorders and diseases as they are readily available in nature and have negligible side effects. In an attempt to identify safe alternatives to NSAIDs, we tested six bioactive compounds from Ginkgo biloba (Ginkgolide A, Amentoflavone, Bilobetin, Ginkgetin, Quercetin, and Bilobalide) for their abilities to inhibit Cyclooxygenase-1, Cyclooxygenase-2 and 5-Lipoxygenase which are inflammation-causing enzymes. Molecular docking experiments using Autodock Vina resulted in binding energy values between -6.6 and -11.9 kcal/mol, comparable to that of control drugs, which indicated that the tested phytocompounds were able to bind strongly to the active sites of the three proteins. Analyses of receptor-ligand interactions using Discovery Studio Visualizer revealed that all the tested compounds formed numerous non-covalent interactions with the surrounding amino acid residues, which confirmed their binding stabilities. Finally, evaluation of their drug likeness based on Lipinski’s rule of five showed that the tested G. biloba compounds possess the potential to be taken as oral drugs to replace conventional NSAIDs.